2018
DOI: 10.22159/ajpcr.2018.v11i3.22790
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hematological Malignancies in Sickle Cell Patients From an Indian Tertiary Care Teaching Hospital

Abstract: Objective: Sickle cell disease (SCD) involves multiple systems and is manifested by variable degree of anemia, acute vaso-occlusive episodes, and chronic organ damage. Small case series have hinted at increased incidence of cancer among SCD patients, but no examination of population-based data in Odisha has been reported. Here, we have reported the association of hematological malignancies and SCD in our region. Methods:In this prospective study, we have documented all the demographic and clinical data of sick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The predominance of AML subtype among these patients is in support of suggestion of increased risk for AML among SCD patients and previous studies done in the same hospital which showed that AML was commoner than ALL 5 , 15 . The predominance of AML among the patients may be attributed to the age distribution of the patients in which AML rather than ALL is commoner.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The predominance of AML subtype among these patients is in support of suggestion of increased risk for AML among SCD patients and previous studies done in the same hospital which showed that AML was commoner than ALL 5 , 15 . The predominance of AML among the patients may be attributed to the age distribution of the patients in which AML rather than ALL is commoner.…”
Section: Discussionsupporting
confidence: 85%
“…Lack of folic acid can affect the genetic and epigenetic integrity of p53, which is a well-characterized tumour suppressor 12 . In folic acid replete, 5 , 10 -Methylenetetrahydrofolate derived from folic acid ingestion donates a methyl group to uracil, converting it to thymine, which is used for DNA synthesis and repair. If folate is limited, imbalances in the DNA precursor pool occur, and uracil may be misincorporated into DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations